1993
DOI: 10.1007/bf01319004
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of different CD4-immunoglobulin constructs against HIV-1 and SIV: immunological characterization, pharmacokinetic data and in vivo experiments

Abstract: The CD4 cell surface antigen belongs to the immunoglobulin superfamily and is the primary receptor for the human immunodeficiency virus 1 (HIV-1). The high affinity interaction between HIV-1 and CD4 is mediated by the viral envelope glycoprotein gp120. Recombinant soluble CD4 (rsCD4) has been shown in vitro to be an effective inhibitor of HIV-1 and HIV-2 propagation in lymphoid cells. A variety of antibody-like molecules were constructed, consisting of different parts of the extracellular domain of CD4 fused t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Several promising monomeric (3)(4)(5), dimeric (6)(7)(8), and tetrameric (9-11) sCD4 derivatives have been tested in animal models and in human clinical trials, but they exhibited modest and transient antiviral activities. Previously, we demonstrated that decreasing the molecular size of D1D2 to a single domain, D1, significantly increased its antiviral activity and reduce its nonspecificity, i.e., interactions with molecules other than the HIV-1 envelope glycoprotein (Env) gp120; a D1 variant (mD1.2) was identified that is also more soluble than D1D2 (12).…”
mentioning
confidence: 99%
“…Several promising monomeric (3)(4)(5), dimeric (6)(7)(8), and tetrameric (9-11) sCD4 derivatives have been tested in animal models and in human clinical trials, but they exhibited modest and transient antiviral activities. Previously, we demonstrated that decreasing the molecular size of D1D2 to a single domain, D1, significantly increased its antiviral activity and reduce its nonspecificity, i.e., interactions with molecules other than the HIV-1 envelope glycoprotein (Env) gp120; a D1 variant (mD1.2) was identified that is also more soluble than D1D2 (12).…”
mentioning
confidence: 99%
“…Expression of a soluble form of receptor, p75-Fc. The ectodomain of the human p75NTR receptor (amino acids 1 to 222) was cloned in fusion with the cDNA from the human IgG1 heavy chain Fc domain (2,30). A plasmid (CD4-Fc) was obtained from Brian Seed (Massachusetts General Hospital); the CD4 coding sequence was excised with XhoI and BamHI restriction enzymes and replaced by the human p75NTR coding sequence (kindly provided by Barbara Hempstead, Cornell University, Ithaca, N.Y.).…”
Section: Methodsmentioning
confidence: 99%
“…The most powerful approach for the localization of the receptor binding site is to select mutants that escape neutralization by a soluble form of a viral receptor: they are named "srr (soluble receptor resistant) mutants." Although neutralizing activity of soluble receptors has been reported for many viruses, such as poliovirus (11,26), rhinovirus (23,36), coronavirus (71,72), human immunodeficiency virus (13,24,30,52,56), measles virus (10), and hepatitis A viruses (51), characterization of srr mutants has only been described in the cases of poliovirus (11,26) and coronavirus (37,38,45,46).…”
mentioning
confidence: 99%
“…A previous study (4) showed that monomeric sCD4 did not inhibit immune functions in monkeys, suggesting it was unlikely to be immunosuppressive in humans. However, the experiment needs to be repeated in humans with higher-order oligomers, because oligomerization of CD4 is required for interaction with MHCII or, presumably, other targets, and the highly potent sCD4 derivatives described above are exclusively multimeric (1,14,22,26). Although sCD4-Fc fusion proteins have been safely administered to a number of humans in several clinical trials, it was uncertain whether long-term treatment would be safe.…”
Section: Vol 85 2011 Engineered Single Human Cd4 Domains 9401mentioning
confidence: 99%
“…Third, the D1 mutants could be more useful than D1D2 to generate candidate HIV-1 therapeutics, not only because of higher potency, but also due to smaller size. The antiviral activities of monomeric (18,32,33), dimeric (22,26), and tetrameric (1,14) human sCD4 as Fc fusion proteins have been evaluated in animal models and human clinical trials. They were well tolerated by patients with no significant clinical or immunologic toxicities and exhibited significant inhibitory activities, such as reductions in plasma viremia and virus titer.…”
Section: Vol 85 2011 Engineered Single Human Cd4 Domains 9401mentioning
confidence: 99%